Valine increases milk fat synthesis in mammary gland of gilts through stimulating AKT/MTOR/SREBP1 pathway†. Issue 1 (15th April 2019) - Che, Long; Xu, Mengmeng; Gao, Kaiguo; Zhu, Cui; Wang, Li; Yang, Xuefen; Wen, Xiaolu; Xiao, Hao; Jiang, Zongyong; Wu, De
Abstract: Lactating mammary glands are among the most active lipogenic organs and provide a large percentage of bioactive lipids and calories for infant growth. The branched-chain amino acid (BCAA) valine is known to modulate fatty acids synthesis in adipose tissue; however, its effects on fat metabolism and the underlying mechanisms in mammary glands remain to be determined. Valine supplementation during late pregnancy significantly increased the contents of total milk fat, triglyceride, sphingomyelin, and polyunsaturated fatty acids in the colostrum of gilts. Further study in porcine mammary epithelial cells (PMECs) confirmed that valine upregulated the phosphorylation levels of AKT-activated MTOR and subsequently induced the nuclear accumulation of sterol regulatory element binding protein 1 (SREBP1), thus increasing the expression of proteins related to fatty acids synthesis and intracellular triacylglycerol content. Inhibition of AKT/MTOR signaling or silencing of SREBP1 in PMECs downregulates the expression of proteins related to fatty acids synthesis and intracellular triacylglycerol content. Our findings indicated that valine enhanced milk fat synthesis of colostrum in porcine mammary glands via the AKT/MTOR/SREBP1 signaling pathway. Abstract : The fatty acid in milk is synthesized by the lactating mammary gland. Branched amino acid valine enhanced fatty acids through stimulating AKT/MTOR/SREBP1 pathway.